EVALUATION OF NATURAL CLIMATIC CONDITIONS IN REALIZED ENERGY EFFICIENT BUILDINGS - Mishel Z. Dib (International Journal of Engineering Technologies and Management Research, 2019)
The analysis and evaluation of the features of spatial architecture layout design, structural and engineering solutions of modern energy-efficient low-rise residential buildings have been conducted, taking into account the climatic zoning of the Earth. Research methods are based on a comparative analysis of the modern case studies focuses on the construction of energyefficient low-rise residential buildings. A number of studies have been devoted to the problem of designing energy-efficient passive houses in a climate like Ukraine, but there is still no common typological basis for designing. Further studies have focused on implementing the passive house standard, as well as realized passive house projects have been launched in different parts of the world. This experience is considered as an example of project practices and norms of Europe, Asia, and Arab countries. These examples were grouped by climatic conditions and analyzed from the point of view possibilities of adopting their feasibility solutions to the particular Ukrainian climate and conditions.